(untitled) (Kronika Bydgoska, 2010)
Among many different institutions forming the judiciary system of the Polish People’s Republic, Committees for Fighting against Speculation and Abuse in Trade (KWS) were attached to the Presidiums of National Councils. The committees were collegial organs established under the August 18, 1951 Resolution of the Council of Ministers — ”On increasing the fighting against speculation and abuse in trade”. In Bydgoszcz, this committee was set up on September 1, 1951. The task of the committees, within their control compe- tence, was to support, among others, the fighting against speculation and other abuse conducted sińce 1947. Until 1954, all committees had to co-operate with regional Branches of the Special Committee for Fighting against Economic Abuse and Harmful Activities (DKS), which co-ordinated this fight. Starting from 1955, the committees (KWS) carried the main load of struggle in the “battlefield”. New power bestowed mainly in the years 1954-1957 extended the rangę of their operations. According to an estimated analysis, the Bydgoszcz KWS controlled about 29,453 shops in the years 1951-1964, and wrote 5,936 criminal reports on about 6,133 different “offences”.